Managing the narrative of sustainable development: "discipline" of an "inefficient" concept. (30th March 2006) - Springett, Delyse
This paper overviews two contested narratives of sustainable development. One employs sustainable development as a key concept in the rhetoric of eco-modernism and 'green business', following a 'managerial' model. The opposing narrative frames the concept as capable of emancipating more democratic and inclusive approaches to living with nature and with each other. Some of the ways in which that emancipatory narrative of sustainable development has been 'disciplined' and 'tamed' by the successful employment of the traditional power of management are considered. The paper draws upon an investigation carried out in New Zealand to identify how sustainable development was being framed at government and corporate level prior to the World Summit on Sustainable Development in 2002. It is concluded that the concept of 'management' of sustainable development was largely driving the debate. However, counter-hegemonic views were also emerging that challenged the managerial narrative in order to address systemic impediments to sustainable development.